The reduction in locomotor activity induced by restraint stress in young male mice involves the downregulation of hippocampal serotonergic and dopaminergic markers - Megumi Furukawa; Nobuo Izumo; Masahiro Toho; Ryoken Aoki; Hiroki Nishijima; Yusuke Nakamura; Yumi Sakai; Yukiko Ishibashi; Haruna Kurono; Takayuki Manabe; Hideo Matsuzaki (IBRO Neuroscience Reports)
The novel coronavirus (COVID-19) pandemic led to widespread restrictions on human activities, including limits on physical activity and public gatherings. In particular, the physical and mental effects of restricting childhood activities such as exercise and play urgently need to be elucidated. In this study, we analyzed the effects of restraint stress on young (4-week-old) and adult (10-week-old) mice using behavioral experiments and gene expression analysis. Restraint stress did not cause a decrease in the expression of BDNF, a depression marker, in the hippocampus, suggesting that it may be a relatively mild form of stress. In young mice, restraint stress caused significant reductions in locomotor activity and sucrose preference. In contrast, in adult mice, no significant difference was observed in locomotor activity or sucrose preference. Increased expression of the XBP-1 gene might be involved in the resistance to endoplasmic reticulum stress and resilience to restraint stress in adult mice. Moreover, serotoninergic and dopaminergic markers were significantly downregulated in young mice exposed to restraint stress. These findings strongly suggest an increased vulnerability to stress during early childhood, which may substantially impact subsequent brain development in children.